ENHANCING BROILER CHICKEN GROWTH AND GUT HEALTH THROUGH MANGIFERA INDICA, LAWSONIA INERMIS, AND CARICA PAPAYA SUPPLEMENTATION - Abdul Sattar Shahani; Imdad Hussain Leghari; Nasir Rajput; Shoaib Ahmed Pirzado; Ghulam Shabir Barham (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This study investigated the effect of dietary supplementation of Mangifera indica (MILP), lawsonia inermis (LILP) and papaya carica (CPLP) leaves powder supplementation on growth performance and gut health of broiler chickens. Six hundred female broiler chickens were divided into five groups: Control group, 0.5% MILP, 0.15% LILP, 0.5% CPLP and 0.58 % mix leaves powder (mixLP) herbs groups. The measured parameters included average daily feed intake (ADFI), body weight gain (BWG), feed conversion ratio (FCR), carcass characteristics and intestinal length. The results showed that (MILP) treated group had significantly higher BWG (61.16 g) and FCR (1.44) compared to the control group. (LILP) treated group had the lowest growth performance but the highest percentage of abdominal fat. (MILP) treated group had improved carcass quality with the highest percentage (72.83%) and percentage of leg muscle (16.81%). (Mix LP) treated group had improved gut health and the longest gut length (191.67 cm). The results of the study indicate that (MILP) promote growth, health and carcass quality, and the (mix LP) supplement has a positive effect on gut health, providing a potential natural alternative to synthetic supplements in poultry production. The (CPLP) and (mix LP) treated groups’ improved intestinal health by showing a favorable balance of gut microflora to propagate Lactobacillus while reducing the population of E. coli. The evidence further supports that (CPLP) supplementation can be an effective natural growth promoter, although the (mix LP) and (CPLP) also contributed positively to gut health and meat quality.